Textural and Surface Characterization of Cork-Based Sorbents for the Removal of Oil from Water - Pintor, Ariana M A; Silvestre-albero, Ana M; Ferreira, Catarina I A; Pereira, Joana P C; Vilar, V J P; Botelho, M S; Rodr, Francisco; Boaventura, Rui A R (Industrial & engineering chemistry research, 2013)
This study evaluates the possibility of adding value to cork granulates, byproducts of cork processing, by using them as biosorbents and precursors of activated carbons. Activation was carried out by impregnation with phosphoric acid followed by pyrolysis under N2 flow. Furthermore, biosorbents were treated with a cationic surfactant and activated carbons were subject to a second pyrolysis under propene with the objective of improving hydrophobicity. Physico-chemical, textural, and surface characterization of the materials was carried out employing, among others, N2 adsorption isotherms, Fourier transform infrared (FTIR) spectroscopy, potentiometric titration, temperature programmed desorption (TPD), and immersion calorimetry. Selected samples were tested in the removal of sunflower oil emulsified in water. Activated carbons with higher surface area and lower amount of acidic surface groups showed higher uptake capacity for sunflower oil
APS
Keywords: biosorbents; cork products; Quercus suber L.; sunflower oil

Use of cork powder and granules for the adsorption of pollutants: a review. - Pintor, Ariana M A; Ferreira, Catarina I A; Pereira, Joana C; Correia, Patrícia; Silva, Susana P; Vilar, Vítor J P; Botelho, Cidália M S; Boaventura, Rui A R (Water research, 2012)
Cork powder and granules are the major subproducts of the cork industry, one of the leading economic activities in Portugal and other Mediterranean countries. Many applications have been envisaged for this product, from cork stoppers passing through the incorporation in agglomerates and briquettes to the use as an adsorbent in the treatment of gaseous emissions, waters and wastewaters. This paper aims at reviewing the state of the art on the properties of cork and cork powder and their application in adsorption technologies. Cork biomass has been used on its original form as biosorbent for heavy metals and oils, and is also a precursor of activated carbons for the removal of emerging organic pollutants in water and VOCs in the gas phase. Through this literature review, different potential lines of research not yet explored can be more easily identified.
Keywords: activated carbon; Adsorption; Cork granules; cork powder; Heavy metals; Pollutants